Proposed Enhancement Plan Towards Quality Health Care and Patient Satisfaction in the Colposcopy Clinic - Wang, Ying (International Journal of Public Health and Medical Research, 2025)
Objective: To assess the correlation between the quality of care in colposcopy clinics and patient satisfaction, and to explore personalized optimization paths based on demographic characteristics. Methods: A cross-sectional study design was employed to conduct a multidimensional assessment of 392 patients. Demographic characteristics were analyzed using descriptive quantitative research methods (primarily married, highly educated women aged 30-39, with a hospital stay of 3-5 days), and a structured quality evaluation was conducted across five quality dimensions (equipment resources, treatment processes, infrastructure, doctor-patient interaction, and environmental comfort). Pearson correlation analysis and multiple regression models were used to explore the relationship between quality indicators and satisfaction. Results: The overall patient satisfaction rate was 87%, with the highest recognition for professional competence of medical staff (91%) and process transparency (89%). Satisfaction among patients under 35 years old was significantly lower than that of those aged 35 and above (68.2% vs 92.7%, p